ASIC Architecture to Determine Object Centroids from Gray-Scale Images Using Marching Pixels - Reichenbach, Marc; Fey, Dietmar; Loos, Andreas (Advances in Wireless, Mobile Networks and Applications, 2011)
The paper presents a SIMD architecture to determine centroids of objects in binary and gray-scale images applying the Marching Pixels paradigm. The introduced algorithm has emergent and self- organizing properties. A short mathematic derivation of the system behavior is given. We show that a behavior describing the computation of object centroids in gray-scale images is easily derived from those of the binary case. After the architecture of a single calculation unit has been described we address a hierarchical three-step design strategy to generate the full ASIC layout, which is able to analyze binary images with a resolution of 64×64 pixels. Finally the latencies to determine the object centroids are compared with those of a software solution running on a common medium performance DSP platform. © 2011 Springer-Verlag Berlin Heidelberg.
UnivIS-Import:2015-04-16:Pub.2011.tech.IMMD.IMMD3.asicar
Keywords: Marching Pixels; emergence and self-organization; image analyzing by moments; image processing in ASIC hardware